2020
DOI: 10.21037/cdt.2020.04.01
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of the endothelin receptor antagonist macitentan in pediatric pulmonary hypertension

Abstract: Background: Macitentan, a dual endothelin receptor antagonist (ERA), was approved in 2014 for the treatment of adults with idiopathic pulmonary arterial hypertension (PAH). Once-per-day dosing and low potential hepatic toxicity make macitentan an appealing therapeutic option for children with PAH, but reports on its use in pediatric patients are still lacking.Methods: Prospective observational study of 18 children [10 male; median age: 8.5, minimum (min.): 0.6, maximum (max.): 16.8 years] with pulmonary hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 44 publications
0
20
1
1
Order By: Relevance
“…However, longitudinal assessment of NT-proBNP in combination with echocardiography is very useful to assess disease progression and/or response to treatment. [41][42][43][44] Meanwhile, additional biomarkers are under consideration and may contribute to future PH management. 12,40 TREATMENT Supportive measures Supplemental oxygen should be supplied when target oxygen saturations are >93% for infants with suspected and >95% for infants with proven PH (Fig.…”
Section: Diagnosis Of Bpd and Bpd-phmentioning
confidence: 99%
See 2 more Smart Citations
“…However, longitudinal assessment of NT-proBNP in combination with echocardiography is very useful to assess disease progression and/or response to treatment. [41][42][43][44] Meanwhile, additional biomarkers are under consideration and may contribute to future PH management. 12,40 TREATMENT Supportive measures Supplemental oxygen should be supplied when target oxygen saturations are >93% for infants with suspected and >95% for infants with proven PH (Fig.…”
Section: Diagnosis Of Bpd and Bpd-phmentioning
confidence: 99%
“…Macitentan has been studied in a small prospective pediatric study and was shown to be safe and efficacious as add-on therapy. 44 Off-label use of macitentan also has been reported in BPD-PH patients. 56 Of note, bosentan lowers circulating sildenafil levels, while the other two ERA, ambrisentan and macitentan, do not.…”
Section: Pharmacotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…After 24 weeks, there was no further increment in exercise capacity in this cohort of patients with different etiologies of PAH (62). Eighteen patients younger than 12 years were prospectively assessed after either switching from sildenafil and/or bosentan to macitentan or who were treatment-naïve (20). Schweintzger et al reported improvements in invasive hemodynamics, tricuspid annular plane systolic excursion (TAPSE) and NT-proBNP values after median 6 months (20).…”
Section: Endothelin Receptor Antagonistsmentioning
confidence: 83%
“…The same holds true for endothelin receptor antagonists: Bosentan is approved for infants with pulmonary arterial hypertension above >1 year of age in Europe and >3 years of age in the U.S., but data on its safety and efficacy in young children with BPD-PH are sparse [ 2 , 3 ]. Recently, we published the first pediatric prospective observational study on the use of macitentan, including five infants with BPD-PH [ 4 ]. We believe that further research on new PH-targeted therapies and the role of early combination therapies might help reduce morbidity and mortality in BPD-PH.…”
Section: To the Editormentioning
confidence: 99%